ANALISIS PENGARUH DANA PIHAK KETIGA, PEMBIAYAAN, PEMBIAYAAN BERMASALAH, DAN LABA TERHADAP CORPORATE SOCIAL RESPONSIBILITY (CSR) BANK MUAMALAT INDONESIA TAHUN 2008 – 2022 - Tamam, Farhan Zaini; Thantawi, Tubagus Rifqy; Mursyidah, Azizah (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
This study aims to determine the Effect of Third Party Funds (DPK), Financing, Troubled Financing and Profits on Bank Muamalat Indonesia's Corporate Social Responsibility (CSR) in the 2008-2022 period. This type of research is quantitative with secondary data collection methods in the form of quarterly financial reports obtained through official documents that have been published from the Financial Services Authority (OJK) and Bank Muamalat Indonesia (BMI) which are accessed and retrieved through their respective official websites. The formulation of the problem in this study is whether there is a partial and simultaneous effect of TPF, Financing, Joint Financing and Profit on CSR? The data analysis used is the classical assumption test, multiple linear regression analysis, t test, F test and the coefficient of determination. The results of the study describe: (1) the DPK variable does not have a significant effect on CSR as evidenced by the sig value of 0.703 > α. (2) The financing variable has no significant effect on CSR as evidenced by the sig value of 0.230 > α. (3) The Troubled Financing variable does not have a significant effect on CSR as evidenced by the sig value of 0.057 > α. (4) Profit variable has no significant effect on CSR as evidenced by a sig value of 0.402 > α. (5) While the simultaneous F test of TPF, Financing, Joint Financing and Profits have a significant effect on CSR as evidenced by the sig value of 0.036 <α.